Constructing and validating measures of Islamic human resource management practices - Hashim, Junaidah; Wok, Saodah (International Business Information Management Association, IBIMA, 2016)
This study aims to construct measures for Islamic HRM practices and also validate the measures. In order to validate the measures, a regression analysis is done between Islamic HRM practices and workplace happiness. This study employed triangulation method where documents analysis (Quran and Hadith), Islamic subject matter experts interviews (Ulama' and Muslim HR managers), and survey (HR managers and employees), were integrated in this study. A total of 681 responses were obtained for this study. This assures of 95% confidence level. The data encompass 172 managers and 509 employees (with a ratio of 1:3) per organisation. This assures of 95% confidence level. The results partially support the hypotheses. The implications of the study are discussed.